Artefact and Artifice: Evaluation of the Skill of Catch-Only Methods for Classifying Stock Status - Kell, Laurence T.; Sharma, Rishi; Winker, Henning (Frontiers in Marine Science, 2022)
In data and capacity limited situations, catch-only models are increasingly being used to provide summaries of the state of regional and global fisheries. Due to the lack of information on stock trends, heuristics are required for initial and final depletion priors. The lack of data for calibration means that results are sensitive to the choice of heuristics. We, therefore, evaluate the value of obtaining additional information for classifying stock status. We found that heuristics alone performed nearly as well as the catch-only model. This highlights that catch-only models cannot be used as part of management control, where data updates are used to monitor the effectiveness of interventions. To implement management for data-poor stocks, additional data and knowledge are therefore required. The value of obtaining additional information for reducing risk due to loss of yield through adopting a risk equivalence approach should be evaluated. This will help identify the value-of-information and prioritise the development of scientific management frameworks that protect marine ecosystems and the well-being of people who have a stake in the resources at regional and local levels.